Kepastian Hukum Notaris Menerapkan Cyber Notary Dalam Verlidjen Akta Notaris Secara Digital - Kinasih, Nadia Pitra (PT Matra Cendikia Abadi, 2024)
The vagueness of legal norms or vague norms in the UUJN, especially Article 15 paragraph (3), affects the implementation of notary authority in the digital era. This ambiguity has the potential to cause problems, especially in the inconsistency between Article 16 paragraph (1) letter m of the UUJN and Article 15 paragraph (3) of the UUJN, which creates a conflict between the obligations and authorities of notaries in making deeds face to face or in person. The purpose of this study is to ensure legal certainty in making notarial party deeds digitally and how the impact of the implementation of cyber notary in Indonesia in making party deeds regarding signing and reading face to face online. This study uses a normative legal research method with a statute-approach and comparative-approach, as well as qualitative analysis. Data were collected through literature studies from primary, secondary, and tertiary legal sources. The conclusion of the study emphasizes the need for clear and comprehensive legal regulations to regulate the use of digital technology in making notarial deeds, including a strong security system and appropriate notary authorization. An important requirement in making an authentic notarial deed is the reading and signing of the deed, which can be done electronically through media such as video conference. Electronic signature or digital signature, it is expected that the making of a notarial deed digitally can be realized with legal certainty guaranteed through harmonization of laws and regulations. The impact of using cyber notary includes ease of access, process efficiency, time flexibility, cost reduction, document security, and regulatory adjustments. Overall, notaries have an important role in non-governmental public services, and the use of technology in making deeds digitally can be an efficient and practical alternative in supporting legal certainty. However, attention is needed to aspects of data security and regulations that are in accordance with technological developments in the digital era. Keywords: Notary; Cyber Notary; Verlidjen